IMPACT OF THE TURNIP MOTH ON AGRICULTURAL CROPS AND EFFECTIVE CONTROL MEASURES IN UZBEKISTAN (Scientific journal of the Fergana State University, 2025)
The turnip moth (Agrotis segetum) is a harmful pest of agricultural crops characterized by high ecological adaptability and significant activity across various ecosystems. This article explores the biological and ecological characteristics of the turnip moth, its geographical distribution, and control measures. Special attention is given to the development of effective management strategies under the conditions of Uzbekistan, particularly in the Fergana Valley.